Threat categories of Vatica mangachapoi should be reassessed - Yu, Haoze; Pei, Xuechen; Zhang, Hui (Frontiers in Forests and Global Change, 2024)
Introduction Asian tropical rainforests have the highest rates of degradation in the world. Consequently, a large decline in Chinese Vatica mangachapoi (a keystone species) had led to its listing in the category of “vulnerable” species by IUCN. However, its current status after decades of conservation efforts remains unknown. Methods Here, we evaluate the current status of Chinese V. mangachapoi. Results and Discussion We found that its population is now dispersed in 14 protected areas, the largest being a coastal forest that contains 96.84% of all the Chinese V. mangachapoi. Compared to their historic records, the age of this forest was estimated at ≤ 70 years. The mono-culturing of V. mangachapoi in this forest, since 1960, has replaced all the older trees, resulting in its extremely high (91%) relative abundance, and an extensively low (only 44) tree species richness. Further, these V. mangachapoi trees now suffer from vine strangulations and severe Amauroderma perplexum infections: 18.5% of V. mangachapoi have died and 75% are at a high risk, thereby creating a threat of its extinction. Although, the other 13 protected areas have a higher tree species richness (152–451), a lower (6.1–25%) relative abundance of V. mangachapoi, and they neither suffer from vine strangulation or disease infections, they contribute to only 3.16% of total Chinese population of this species. Therefore, an immediate revision of threat status of this species in IUCN, from vulnerable to endangered, is warranted. Further, a change in planting patterns, from monocultures to mix-plantations of native species, is needed to promote biodiversity and restrict other biotic challenges so that this species is not extinct.